Empowerment of Appropriate Technology for Making Effective Compost from Biogas and MOL Waste for the Community - Riska Rahmasari; Filsuffi Mutaqqin; Beny Suyanto; Frida Hendrarinata; Izzul Maromi; Dini Mutiatul Millah; Winarista Priska K (Pusat Unggulan Ipteks Poltekkes Kemenkes Surabaya, 2023)
Every human activity in their daily activities always produces waste that pollutes the environment. Thiscan be minimized by using it as compost. So it is necessary to introduce appropriate technology for thecommunity in the manufacture of compost using effluent digester waste from biogas waste and localmicroorganisms. Breeders who have related materials are invited to make fertilizer. Apart from being anutrient supplier, the local microorganism solution also acts as a bioreactor component whose job is tomaintain optimal plant growth processes. The function of a bioreactor is very complex, includingsupplying nutrients through the exudate mechanism, controlling microbes according to plant needs,maintaining stability of soil conditions towards ideal conditions for plant growth, even controllingdiseases that can attack plants. plant. It is recommended to check the levels of N, P, K and C/N in thecompost produced, so that standards are maintained.